Current State of Knowledge About Plastics` Ability to Sorption - Worobiczuk, Mateusz; Naumowicz, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Plastic pollution is and will be a problem for humanity to deal with for decades to come. The main cause for concern is plastic debris of microsizes, that has been detected in many worrying locations, e.g. human body. Microplastic can carry many substances. It`s possible for many substances, including toxins, to accumulate on plastic surface. This review pertains to the compilation of the newest scientific information regarding plastic`s ability to sorption. The methodological approach as well as mathematical models used in studies pertaining to this topic have been demonstrated. The type of plastic, the matrix and state of microplastic sample have been described to be affecting sorption on plastic. Some problems with methodology in compiled sorption studies have been outlined. It was concluded that more research is needed to be done to fully grasp this topic.
Keywords: plastic pollution; microplastics; sorption on plastic surface